Unbreakable : an autobiography - Kom, M. C. Mary (Noida HarperCollins, 2013)
Born to parents who were landless agricultural labourers in the state of Manipur in Northeast India, Mary Kom's story is one of relentless struggle and unflagging passion for boxing. A childhood of hard labour prepared her body for the sport as well as any fitness training might have. Her own will and aggression carried her through the minefield of politics that any sport in India is. Nimble of foot and pulling no punches, the boxing ring was her domain. M.C. Mary Kom is not yet ready to call it a day, but here she tells her story so far, no holds barred -- her tough childhood, her rebellions and how she held her own in the male world of boxing. It's all packed into this inspiring, exhilarating tale of a woman who faced impossible odds in a man's world -- and won.
Keywords: Women boxers; Sports; Autobiography